Rhizosphere mycobiome diversity in four declining Mediterranean tree species - Diez-Hermano, Sergio; Poveda, Jorge; Niño-Sanchez, Jonatan; Bocos-Asenjo, Irene Teresa; Peix, Álvaro; Martín-Pinto, Pablo; Diez, Julio Javier (Frontiers in Forests and Global Change, 2023)
Forests in the Mediterranean basin are currently in decline. Their resilience has been eroded as a result of climate change and anthropogenic impacts, making them vulnerable to increasingly frequent episodes of drought, fire and the spread of pests and diseases. The impact of these natural and anthropogenic events on soil biodiversity is of particular concern, as the soil fungal community plays a key role in ecosystem homeostasis. In order to analyse the relationship between soil health status and fungal diversity, soil samples were collected from declining Mediterranean forests of Castanea sativa (chestnut), Quercus ilex (holm oak), Quercus suber (cork oak) and Quercus pyrenaica (Pyrenean oak). A metabarcoding study was carried out by sequencing the ITS genomic region. A total of 674 fungal genera were found. It has not been possible to explain the differences in health status from the fungal genera found exclusively on declining forest soils, as none of them have been described as pathogenic. Healthy chestnut soils were characterised by a high alpha diversity and a higher abundance of the genus Metarhizium. No differentially abundant genera were found in any of the other forest species tested. Declining chestnut soils harboured more abundance of ectomycorrhizae and soil saprotrophs than healthy samples. Ectomycorrhizae were the dominant lifestyle in all oak species regardless of health status, whereas arbuscular mycorrhizae were preferentially found in declining cork oak soils. This work highlights the resilience of fungal communities of soil against decline and highlights the need to further investigate its relationship with the forest's ability to cope with the challenges of climate change.